Longitudinal Antibody Responses in People Who Inject Drugs Infected With Similar Human Immunodeficiency Virus Strains. (4th October 2019) - Redd, Andrew D; Doria-Rose, Nicole A; Weiner, Joshua A; Nason, Martha; Seivers, Matthew; Schmidt, Stephen D; Laeyendecker, Oliver; Martens, Craig; Bruno, Daniel; Keele, Brandon F; Raju, Nagarajan; Georgiev, Ivelin S; et al.
Abstract: Background: Multiple factors influence the human immunodeficiency virus (HIV) antibody response produced during natural infection, leading to responses that can vary in specificity, strength, and breadth. Methods: People who inject drugs identified as recently infected with HIV (n = 23) were analyzed for clustering of their viral sequences (genetic distance, <2%). Longitudinal antibody responses were identified for neutralizing antibody (Nab) potential, and differences in antibody subclass, specificity, and Fc receptor ligation using pseudovirus entry and multiplexed Fc array assays, respectively. Responses were analyzed for differences between subject groups, defined by similarity in the sequence of the infecting virus. Results: Viral sequences from infected individuals were grouped into 3 distinct clusters with 7 unclustered individuals. Subjects in cluster 1 generally had lower antibody response magnitudes, except for antibodies targeting the V1/V2 region. Subjects in clusters 2 and 3 typically had higher antibody response magnitudes, with the Fv specificity of cluster 2 favoring gp140 recognition. NAb responses differed significantly between clusters for 3 of 18 pseudoviruses examined ( P < .05), but there were no differences in overall NAb breadth ( P = .62). Discussion: These data demonstrate that individuals infected with similar viral strains can generate partially similar antibody responses, but these do not drastically differ from those in individuals infected with relatively unrelated strains. Abstract : This study found that people infected with genetically similar human immunodeficiency virus variants can develop related antibody responses to the virus. However, these shared antibody responses do not drastically differ from those found in individuals infected with dissimilar viruses.